Respuesta :

Answer:  x = 3, y = 1, z = 2

Step-by-step explanation:

EQ 1:   x  -   y  - z = 0

EQ 3: -x + 2y + z =  1

                  y       = 1

EQ 2: 2x - 3y + 2z = 7  →  1(2x - 3y + 2z = 7)  →  2x - 3y + 2z = 7

EQ 3:  -x + 2y +  z = 1   → -2( -x + 2y +  z = 1)  → -2x + 4y + 2z = 2

                                                                                      y + 4z = 9

                                                                    y = 1  ⇒     1  + 4z = 9

                                                                                            4z = 8

                                                                                              z = 2

Input y = 1 and z = 2 into one of the equations to solve for x:

EQ 1: x - y - z = 0

        x - (1) - (2) = 0

        x - 3 = 0

        x = 3

Check:

EQ 2: 2x - 3y + 2z = 7

         2(3) - 3(1) + 2(2) = 7

          6    -  3    +  4    = 7

                3        +  4    = 7

                               7   =  7   [tex]\checkmark[/tex]

ACCESS MORE